Investigation of a semi-submersible floating wind turbine in surge decay using CFD. Issue 1 (2nd January 2020) - Burmester, Simon; Vaz, Guilherme; Gueydon, Sebastien; el Moctar, Ould
ABSTRACT: The hydrodynamic damping estimation of the surge motion and the flow characteristics of a moored semi-submersible floating offshore wind turbine is the focus of this paper. The numerical surge decay tests were investigated using a Reynolds-Averaged Navier–Stokes solver. Solution verification on the numerical simulations was performed by estimation of the numerical errors and uncertainties. A linear stiffness matrix and a non-linear quasi-static mooring model were used in the equations of motion. Several surge decay simulations were performed to understand the effects of wave radiation, coupled motions and non-linear moorings on the hydrodynamic damping and the flow field around the floater. The numerical results were compared with experimental data. The free surface had major effects on the hydrodynamic damping and the flow field.